Parametric optimization and sensitivity analysis of the integrated Taguchi-CRITIC-EDAS method to enhance the surface quality and tensile test behavior of 3D printed PLA and ABS parts - Mst. Nazma Sultana; Omar Shadat Sarker; Nikhil Ranjan Dhar (Heliyon)
3D printing is a popular and cost-effective method for producing lightweight engineering parts with enhanced characteristics and detailed prototypes. Nevertheless, the quality of the print can be diminished by the selection of improper parameter settings. This investigation explored the impact of printing factors on the tensile behavior of polylactic acid (PLA) and Acrylonitrile Butadiene Styrene (ABS) specimens. Experimental investigations were conducted to investigate the effects of infill pattern (grid, 2D, and 3D honeycomb), layer thickness (0.10, 0.15, and 0.20 mm), infill percentage (30 %, 50 %, and 70 %), and printing material on surface roughness and tensile characteristics where an irregular dependency was identified. In this scenario, the Evaluation based on Distance from Average Solution (EDAS) Method was integrated with Taguchi and Criteria Importance through Inter-criteria Correlation (CRITIC) to prevent inconsistent judgments with a minimal number of experiments. PLA printed parts with 2D honeycomb design, 0.10 mm layer thickness, and 50 % infill provided the optimum results within the declared boundary conditions. The robustness and sensitivity of the employed MCDM method were assessed through a comprehensive analysis. The weights determined through other techniques, including the equal method, principal component analysis (PCA), and Entropy, were subsequently compared to CRITIC. The results indicated a stronger correlation between PCA and CRITIC. Furthermore, the Pearson correlation matrix results indicated that EDAS was significantly correlated with the MOORA method in comparison to the other methods (ARAS, WASPAS, GRA, COPRAS, and CODAS).